Lung microbiome in children with hematological malignancies and lower respiratory tract infections - Zhang, Yun; Ning, Haonan; Zheng, Wenyu; Liu, Jing; Li, Fuhai; Chen, Junfei (Frontiers in Oncology, 2022)
Background:Respiratory infectious complications remain a major cause of morbidity and mortality in children with hematological malignancies. Knowledge regarding the lung microbiome in aforementioned children is limited. Methods: A prospective cohort was conducted, enrolling 16 children with hematological malignancies complicated with moderate to severe lower respiratory tract infections(LRTIs), versus 21 LRTIs children with age, gender, weight, infection severity matched, with no underlying malignancies, to evaluate the lung microbiome from bronchoalveolar lavage fluid samples in different groups. Results: Lung microbiome from children with hematological malignancies and LRTIs showed obviously decreased α and β diversity, increased microbial function in infectious disease:bacteria/parasite, drug resistance:antimicrobial and human pathogenesis than control group, significantly reduced proportion of Firmicutes, Bacteroidota, Actinobacteriota , increased Proteobacteria at the phylum level, distinctly elevated Parabacteroides, Klebsiella, Grimontia, Escherichia_Shigella, unclassified_Enterobacteriaceae at the genus level than the control group. Besides, it was revealed that α diversity(Shannon), β diversity(Bray Curtis dissimilarity), Proteobacteria at the phylum level, unclassified_Enterobacteriaceae and Escherichia_Shigella at the genus level were significantly negatively associated with hospitalization course whereas Firmicutes at the phylum level was established positively correlated with hospitalization course. Conclusions: Children with hematological malignancies and LRTIs showed obviously decreased α and β diversity, significantly increased function in infectious disease pathogenesis, antimicrobial drug resistance, and unfavorable environment tolerance. Besides, α diversity(Shannon), β diversity(Bray Curtis dissimilarity), Proteobacteria maybe used as negative correlated predictors for hospitalization course in these children whereas Firmicutes as a positive correlated predictor.